Co-resident grandparent and maternal employment. A Northern Ireland cross-sectional administrative data analysis - Miller, Ana Corina; O'Reilly, Dermot; Wright, David (International Journal of Population Data Science, 2024)
The trade-off between the costs of childcare provision and the benefits of having an increased proportion of women, particularly women with dependent children, in employment is one of the most taxing social issues for Western governments. In countries like Northern Ireland, the limited subsidised childcare provision for preschool and primary school children has been partially offset by a rise in informal childcare though this has been considerably hard to assess both in terms of magnitude and effect. Using the entire 2011 Census cohort of mothers with children aged 1 to 16 years of age, we argue that co-resident grandparents have a substantial positive impact on maternal labour force participation in Northern Ireland. The presence of a co-resident grandparent was associated with an increase of 3.7 percentage points in employment for single-parent mothers and 2 percentage points for mothers in two-parent households. Mothers with co-resident grandparents report an increase of 2.7 percentage points for a single mother and of 3.7 percentage points for a mother in a two-parent household being in full-time employment than mothers without. Overall, the presence of a co-resident grandparent was associated with at least a 3.2 percentage point increase in labour force participation among mothers with primary-school-age children.